Quine between Russell's extreme realism and Carnap's extreme relativism : a coherent alternative? - Forde, Alan (Trinity College (Dublin, Ireland). Philosophy Department, 2006)
In the philosophical literature of the past century few if any philosophers present a greater wealth of ideas or pose more important problems than W. V. Quine. In spite of the diversity of his contributions to philosophy, it is clear that they form a systematic unity. It is precisely the systematic unity of his thought that has established Quine as the most influential philosopher of the past century. The basis of Quine's system lies in his revival of "naturalism": this is the view that there is no vantage point outside science; philosophy is continuous with science not distinct from it or prior to it; hence, it is science that tells us what exists and science that tells us how we know what exists. The complex system of interlocking positions that make up Quine's naturalism have shaped the concerns of the philosophical community for the past fifty years.
Keywords: Philosophy, Ph.D.; Ph.D. Trinity College Dublin